Breaking Connectivity Barriers in Digital Mining with a Resilient LTE-WLAN Overlay Network - Rizqi Pratama (Green Publisher Indonesia, 2025)
Digital transformation is essential to improving productivity and sustainability in mining operations. However, complex topography—such as deep pits, high walls, and uneven terrain—creates significant challenges for wireless communication infrastructure. Standalone Wi-Fi networks suffer from unstable signals, while LTE networks experience blind spots in obstructed areas. Field assessments at a mining site in South Kalimantan, Indonesia, revealed that 21.6% of operational zones recorded LTE RSRP levels below –110 dBm, disrupting key operational connectivity. This study proposes a hybrid LTE–WLAN overlay architecture using dynamic load-balancing and failover mechanisms to ensure reliable, high-speed communication. The approach offers environmental adaptability, network flexibility, and cost-efficiency by combining LTE’s wide-area coverage with WLAN’s localized stability. Simulation results show FTP throughput exceeding 94%, RSRP above –100 dBm in 92.43% of areas, and SINR above 98.40%, with seamless handovers and 100% E-RAB success rates. Bandwidth analysis highlights major fluctuations in standalone Wi-Fi (0–2000 Kbps), whereas the overlay solution maintains stable 2–6 Mbps bandwidth. Connection quality in overlay networks remains above 98%, compared to frequent drops below 50% in standalone Wi-Fi. These findings demonstrate that the LTE-WLAN overlay architecture significantly enhances communication stability and performance across challenging mining environments, addressing the identified connectivity gaps through practical, field-validated implementation. Connection quality and bandwidth utilization are identified as key success parameters, confirming that the proposed solution is practical, scalable, and effective for supporting real-time monitoring, IoT integration, and industrial automation in digital mining.